Experimental Design to Understand the Student Loan Decision: A Methodological Note. (3rd September 2016) - Cho, Soo Hyun; Mountain, Travis P.; Porto, Nilton; Kiss, D. Elizabeth; Gutter, Michael S.; Griesdorn, Tim
Abstract : The purpose of this study was to introduce a relatively new methodology of combining experimental design and survey data in the context of personal financial decision making. The NC2172 research team collected data online while manipulating framing effects, aspirations, and gender on hypothetical student loan decisions. The paper describes the development of the experimental conditions, demonstrates the effectiveness of the manipulations, and explains the importance and structure of random assignment of respondents across conditions. It seeks to guide future attempts utilizing experimentally designed online surveys by providing potential benefits and challenges.